Influence of antioxidants for improving animal production: lamb meat characteristics - De Marzo, D.; Nicastro, Francesco; Facciolongo, Anna Maria; Degiorgio, F.; Toteda, Francesco; Nicastro, A. (Progress in Nutrition, 2014)
Thirty Gentile di Puglia and thirty Val del Belice breeds lambs have been bred. They were fed with weaning feed over a 30-day period, and later with growth feed added with omega-3. The most representative fatty acid was DHA. Lambs were divided in two groups according to the following treatments: First group: Post weaning rationing with no omega-3 in diet; Second group post weaning rationing with diet containing 2% of omega-3; Lambs were slaughtered at 110 days of age and the carcasses were chilled at 3° C for 24 h. After the carcass was sectioned in quality cuts. The leg and rib cuts were broken down into fractions tissue. A sample of the Longissimus dorsi muscle was subjected to quality analysis. Polyunsaturated fatty acids were analyzed on the intramuscular fat. Important results were found in lambs fed with omega-3 addition, in order to improve the color and fatty acids. Further investigation is needed to define the optimal dose of integration.